Economic analysis of the implementation of an LED lighting system in a dark house: A case study - da Rosa, Carolina Obregão; Garcia, Rodrigo Garófallo [UNESP]; da Costa, Jaqueline Severino; Nääs, Irenilza de Alencar; Lima, Nilsa Duarte da Silva (My University, 2017)
The use of the Light Emitting Diode (LED) in broiler chicken production is a trend practically irreversible as it happened with the use of compact fluorescent light (FCL) in substitution of the incandescent lamps. As LED is a new technology, there is a shortage of results regarding the economic feasibility of a LED lighting system in broiler chicken production especially considering that the price of this light source is yet high. Therefore, this research aimed to analyze the economic feasibility if LED lighting in broiler chicken production. A case study was carried out comparing the energy consumption of two dark houses systems being one with FCL lighting, and the other using LED lighting. Both houses had the same structural characteristics and production capability. The following indicators were calculated using deterministic investments analysis: Reduction in Lamp Price (TRPL), Net Present Value (NPV), Annual Internal Rate of Return (IRR), Profitability Index (IL), and Profitability Rate (TR). The cash flows and the initial cost of the project using LED lamps were evaluated, and their indicators were found. The results suggest the unfeasibility of implementing LED lighting in dark house considering the current LED lamp values. If the cost of this input is reduced by approximately 35%, LED lighting might be a feasible alternative in the production of broiler chickens, as the results indicate that the use of the light emitting diode saved 72% of kWh, when compared to the use of the CFL.
Keywords: Economic viability; Lighting system; Poultry